The effects of leadership and gender on dyad creativity - Tidikis, Viktoria (Psichologija, 2015)
The present article considers how leader emergence and leadership style affect creativity in dyads of varying gender composition. While there is extensive research regarding dominative dynamics within group settings and their impact on creativity, less has focused on gender as an additional influencer to the creative process and its effect on dyad efficiency. To this end, leadership emergence and leadership style within dyads of varying gender composition was examined. Creativity was measured using five insight problems. One hundred and eight participants participated in this experiment and were assigned to either same gender or mixed gender dyads, resulting in an all-male, all-female, or mixed gender pairs. Dyads with emerged leaders solved more problems and solved them faster than dyads without leaders. Pairs with autocratic leadership solved problems faster, however they solved less problems correctly as compared to groups with the democratic leadership style. Leaders were more likely to emerge in an all-male dyad, compared to other conditions. And while all-male dyads solved problems faster, there was no difference in solution rates among different gender conditions. In all, examination of the creative problem-solving behaviors in dyads of the varying gender composition brought a new understanding of factors influencing creativity in small groups.